Urban Voids: renewal and regeneration experiences in Naples - Punziano, Gabriella; Terracciano, Anna (TeMA - Journal of Land Use, Mobility and Environment, 2017)
City and society, by definition unstable, constantly redefine the relation between places and actors, generating frequently critical circumstances that are addressed by only temporary solutions. The unexpected and uncontrolled social conditions and lifestyles build new geographies and centres. The activities of dismantlement, degradation, reuse, abandonment, and land use, continuously blend materials and relationships and requires rethinking the methods of describing the city and defining a new grammar of representation closer to the contemporary space, materials, actors, and relationship. Focusing on experiences of renewal, regeneration and recycle, the objective of this exploratory study is to investigate their different impacts in a well-known complex urban system as Naples. The study emphases on the urban and social dimensions, favouring a descriptive and visual perspective from those who experience life in the city, considering the processes implemented by local actors and the reactions of inhabitants to these processes. Infact in Naples, despite its critical conditions, it is possible to trace signals indicating small informal practices of re-use in vacant or ruined areas, as well as existing small-scale clustering processes to re-adapt single buildings or spaces for new uses. So, this study uses an innovative methodology to investigate this emerging implied writing as a set of latent questions and needs expressing renewal, regeneration and recycle phenomena. Through this technique, we will focus on the images of the city and its development trajectories.